2019
DOI: 10.1002/iub.2002
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the anti‐cancer drug elesclomol that forms a redox‐active copper chelate as a potential anti‐tubercular drug

Abstract: The observations that the innate immune system employs copper to eliminate bacterial infection and that resistance to copper enhances virulence of Mycobacterium tuberculosis (Mtb) prompted us to examine the effects the anti‐cancer agent elesclomol on Mtb. As a bis‐thionohydrazide, elesclomol chelates with copper to form a copper complex in situ that via redox cycling of the metal ion greatly enhances oxidative stress in tumour cells. Here, we demonstrate that elesclomol is relatively potent against Mtb H37Rv w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Using murine, human and zebrafish models, the authors also established broad applicability of elesclomol as a potential therapeutic agent to treat disorders of mitochondrial and cellular copper metabolism. In another study, elesclomol was shown to be a relatively potent bactericidal against a laboratory strain and multidrug resistant clinical isolates of Mycobacterium tuberculosis ( Mtb ), and to display additive interactions with known tuberculosis drugs, such as isoniazid and ethambutol, and a synergistic interaction with rifampicin [32]. Interestingly, elesclomol exhibited a >65-fold increase in activity against Mtb in the presence of copper compared to non-copper supplemented growth medium.…”
Section: Discussionmentioning
confidence: 99%
“…Using murine, human and zebrafish models, the authors also established broad applicability of elesclomol as a potential therapeutic agent to treat disorders of mitochondrial and cellular copper metabolism. In another study, elesclomol was shown to be a relatively potent bactericidal against a laboratory strain and multidrug resistant clinical isolates of Mycobacterium tuberculosis ( Mtb ), and to display additive interactions with known tuberculosis drugs, such as isoniazid and ethambutol, and a synergistic interaction with rifampicin [32]. Interestingly, elesclomol exhibited a >65-fold increase in activity against Mtb in the presence of copper compared to non-copper supplemented growth medium.…”
Section: Discussionmentioning
confidence: 99%
“…The redox-active phenothiazine methylene blue, which is structurally related to the phenoxazine PhX1, potently synergizes the action of artemisinins against the malaria parasite through enhanced production of reactive oxygen species (ROS), as described in detail elsewhere ( 101 ). Given that M. tuberculosis has a well-defined oxidative stress response ( 102 104 ), it was expected that the redox-active phenoxazine PhX1 or the structurally related clofazimine ( 34 ), in combination with the amino-artemisinin WHN296, would promote the production of ROS, thus explaining the synergism seen against M. tuberculosis .…”
Section: Discussionmentioning
confidence: 99%
“…Because pathogens with multidrug resistance are emerging and new effective antibiotics against them are lacking, metal-containing coordination compounds have become of interest as antibacterial agents. The effectiveness of copper coordination compounds in the treatment of bacterial and fungal infections was mentioned above (coordination compounds 3 and 5 with antibacterial and antifungal activity [39] and Escimolol-based coordination compound 13 in Mtb treatment [48]). A copper-based coordination compound 31 with antimalarial activity against Plasmodium falciparum was developed by [63] (Figure 9).…”
Section: N/n-donor Ligandsmentioning
confidence: 99%
“…(Table 3) Table 3. Effect of copper on antimycobacterial activity of ligand L13 against Mtb H37Rv [48]. Cu-ATSM 14 is a biologically active copper coordination compound based on thiosemicarbazides ( Figure 6).…”
Section: N-and S-donor Ligandsmentioning
confidence: 99%
See 1 more Smart Citation